1972
DOI: 10.1111/j.1365-2478.1972.tb00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Number and Spacing of Sensors on the Effectiveness of Seismic Arrays*

Abstract: Résumé De préférence, les sismographes seront disposés dans un lieu sans bruit, oú il n'y aurait pas besoin de patternes. Par contre, si les bruits sont tels qu'une patterne est nécessaire, l'objectif de la patterne est d'améliorer le rapport signal/bruit et donc de rendre le signal le plus utile possible. La patterne sera dessinée en fonction des charactéristiques du signal, des charactéristiques du bruit, et de la géologie du site. Il a été démontré que, dans le sens pratique, l'opération optimum sur les don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

1974
1974
2015
2015

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
1
0
3
Order By: Relevance
“…The functional flow of data from LASA through the SDAC/LASA system is: 1) data acquisition; 2) detection processing; 3) event processing; 4) experimental operations console (EOC) editing; and 5) publishing of the Daily Earlier studies of the effects of reducing the number of elements at LASA (Hartenberger, 1967;Hartenberger and Van Nostrand, 1970) have shown that the signal-to-noise ratio loss is less than 2db compared to that for the original 525 sensor array when the number of elements is reduced to 119 or 51 with minimum sensor spacing of 3km or 6km respectively. All of the data used in the earlier studies were prefiltered (0.4-3.0 Hz), were beamed to the known opicentral locations, and were corrected for travel-time anomalies (Chiburis, 1968).…”
mentioning
confidence: 99%
“…The functional flow of data from LASA through the SDAC/LASA system is: 1) data acquisition; 2) detection processing; 3) event processing; 4) experimental operations console (EOC) editing; and 5) publishing of the Daily Earlier studies of the effects of reducing the number of elements at LASA (Hartenberger, 1967;Hartenberger and Van Nostrand, 1970) have shown that the signal-to-noise ratio loss is less than 2db compared to that for the original 525 sensor array when the number of elements is reduced to 119 or 51 with minimum sensor spacing of 3km or 6km respectively. All of the data used in the earlier studies were prefiltered (0.4-3.0 Hz), were beamed to the known opicentral locations, and were corrected for travel-time anomalies (Chiburis, 1968).…”
mentioning
confidence: 99%
“…Η απόσταση μεταξύ των αισθητήρων μίας σεισμικής διάταξης είναι η παράμετρος, που καθορίζει τη μέγιστη τιμή κυματαριθμού, που μπορεί να διακριθεί από τη δεδομένη διάταξη και ελέγχει το βαθμό συσχέτισης του θορύβου και τη συνοχή των σεισμικών σημάτων (Hartenberger and van Nostrand, 1972). Η επιλογή της κατάλληλης απόστασης μεταξύ των στοιχείων της διάταξης, η οποία μπορεί να μην είναι ενιαία για όλα τα ζεύγη (Kvaerna, 1989), πραγματοποιείται μέσω μίας μελέτης συσχέτισης του εδαφικού θορύβου για την περιοχή εγκατάστασης της διάταξης.…”
Section: σχεδιασμός σεισμικών διατάξεωνunclassified
“…Οι προκύπτουσες καμπύλες παρέχουν πληροφορίες για τη βελτίωση του λόγου του σήματος προς το θόρυβο, που μπορεί να επιτύχει η σεισμική διάταξη, για κάθε διαφορετική γεωμετρία (Mykkeltveit et al, 1983. Γενικά, πάντως η αποτελεσματικότητα μίας διάταξης είναι συνάρτηση τόσο της απόστασης μεταξύ των αισθητήρων αυτής, της έκτασης, που αυτή καταλαμβάνει και του αριθμού των αισθητήρων, με μόνο τους δύο από τους τρεις αυτούς παράγοντες να μπορούν να θεωρηθούν ως ανεξάρτητες μεταβλητές (Hartenberger and van Nostrand, 1972).…”
Section: σχεδιασμός σεισμικών διατάξεωνunclassified
See 1 more Smart Citation